Land Evaluation and Suitability for Development of Sorghum (Sorghum Bicholor L.) on Peat Land - Juniarti Juniarti; Nofrita Sandi; Afrima Sari; Asdi Agustar; Dyah Puspita Sari (JOURNAL OF TROPICAL SOILS, 2026)
Sorghum (Sorghum bicolor L.) is an annual cereal crop with high adaptability to marginal and acidic environments, making it a promising option for peatland development in Indonesia. This study evaluated land suitability for sorghum cultivation in West Sumatra, Indonesia, using purposive sampling and field survey methods at the regency scale, in accordance with the FAO land evaluation criteria. Land characteristics were analyzed based on climatic, soil, and hydrological parameters. The results show that three peatland types in the study area are classified as moderately suitable with nutrient retention limitations (S2nr). These peatlands are characterized by average temperatures of 25–27 °C, annual rainfall below 2,000 mm, relative humidity below 75%, good drainage, peat depths exceeding 60 cm, and acidic soil conditions (pH 4.4–5.1). Low availability of nitrogen, phosphorus, and potassium was identified as the primary limiting factor for sorghum cultivation. Overall, the findings indicate that peatlands in West Sumatra have substantial potential for sustainable sorghum development, provided that appropriate soil fertility and nutrient management strategies are implemented.